Constitutive models for rubber IX : proceedings of the 9th European Conference on Constitutive Models for Rubbers, (ECCMR IX), Prague, Czech Republic, 1-4 September 2015 /: proceedings of the 9th European Conference on Constitutive Models for Rubbers, (ECCMR IX), Prague, Czech Republic, 1-4 September 2015. ([2015]) - Unknown
No abstract available